Off-Pump Tricuspid Annuloplasty through a Direct Transatrial Approach: Early Results - Andreas, Martin; Werner, Paul; Laufer, Guenther; Sauer, Jude (The Thoracic and Cardiovascular Surgeon, 2019)
Severe tricuspid regurgitation constitutes a growing disease burden. Conventional surgery for tricuspid valve disease has an increased risk while several interventional procedures are currently under clinical investigation, yet do not offer comprehensive solutions. We investigated a novel surgical approach for off-pump beating-heart tricuspid annuloplasty in circulating blood through a single port in the right atrium. Early feasibility results in preclinical porcine in vivo studies encourage further development of this approach, combining the proven concept of surgical annuloplasty with the benefits of minimally invasive off-pump procedures in a hybrid setting.
Keywords: tricuspid valve; off-pump surgery; minimally invasive surgery; tricuspid regurgitation; tricuspid annuloplasty